THE EFFECT OF COMPENSATION AND WORK DISCIPLINE ON WORK PRODUCTIVITY: THE MEDIATING ROLE OF EMPLOYEE PERFORMANCE AT PT BANK ACEH SYARIAH MAIN BRANCH OFFICE, BANDA ACEH - Khalid Malvi; Kurnia Asni; Irwan Safwadi; Fitria (CV. Radja Publika, 2026)
This study examines the effects of compensation and work discipline on work productivity through employee performance at PT Bank Aceh Syariah Main Branch Office, Banda Aceh. Using a quantitative survey approach, data were collected from 153 permanent employees selected from a population of 251 employees. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings indicate that compensation and work discipline have positive and significant effects on both employee performance and work productivity. Employee performance also positively influences work productivity and partially mediates the relationships between compensation, work discipline, and work productivity. Work discipline emerged as the strongest predictor of employee performance, while employee performance was identified as the most influential determinant of work productivity. These findings highlight the importance of strengthening compensation systems and promoting work discipline to enhance employee performance and sustain organizational productivity in the Islamic banking sector.